The Matrix - Silver, Joel.; Wachowski, Lilly, 1967-; Wachowski, Lana, 1965-; Reeves, Keanu; Fishburne, Laurence, III, 1961-; Moss, Carrie-Anne, 1970-; Weaving, Hugo, 1960-; Foster, Gloria, 1936-2001.; Pantoliano, Joe.; Davis, Don, 1957-; Warner Bros. Pictures (1969- ); Village Roadshow Pictures; et al. (Burbank, CA : Warner Home Video, 2001)
In an anti-utopian future, the real world as we know it is nothing more than a computer construct, created by an all-powerful artificial intelligence. A small group of humans has found a way out of the construct, and is now fighting for the future of the human race
Special features: DVD: Commentary track by Carrie-Anne Moss, editor Zach Staenberg and visual effects supervisor John Gaeta ; Isolated musical score with commentary by composer Don Davis ; Production notes ; Theatrical trailer ; Behind-the-scenes documentary "HBO First Look: Making the Matrix" ; Hidden special effects documentaries: "What is Bullet Time?" and "What is the Concept?" ; Nine behind-the-scenes featurettes -- DVD-ROM (only playable on Windows 95 or better computers with DVD-ROM drives): Special Web events and links ; Screenplay and storyboards ; 7 special essays and articles ; Original theatrical Web site ; Theatrical trailer sampler ; Questions and answers about "The one."
Warner Home Video: 17737
Director of photography, Bill Pope ; editor, Zach Staenberg ; music, Don Davis
Keanu Reeves, Laurence Fishburne, Carrie-Anne Moss, Hugo Weaving, Gloria Foster, Joe Pantoliano
DVD format
Closed-captioned
Keywords: Feature films; Science fiction films; Video recordings